Update on Ocular Oncology - Mahesh P Shanmugam; Rajesh Ramanjulu; Shyamal Dwivedi (Delhi Journal of Ophthalmology)
Medicine is an ever-changing subject. With the current developments, diagnosing and treating of patients has reached newer heights. This article describes the newer developments in ocular oncology particularly retinoblastoma (most common intra-ocular tumor in children, melanoma (most common intra-ocular tumor) and haemangioma (a common tumor presenting from young to adult).